Ethical dilemmas in psychotherapy : positive approaches to decision making - Knapp, Samuel; Gottlieb, Michael C.; Handelsman, Mitchell M. (American Psychological Association, 2015)
"New and experienced psychotherapists alike can find themselves overwhelmed by an ethical quandary where there doesn't seem to be an easy solution. This book presents positive ethics as a means to overcome such ethical challenges. The positive approach focuses on not just avoiding negative consequences, but reaching the best possible outcomes for both the psychotherapist and the client. The authors outline a clear decision-making process that is based on three practical strategies: the ethics acculturation model to help therapists incorporate personal ethics into their professional roles; the quality enhancement model for dealing with high-risk patients who are potentially harmful, and; ethical choice-making strategies to make the most ethical decision in a situation where two ethical principles conflict. Throughout the decision-making process, psychotherapists are encouraged to follow four basic guidelines: Focus on overarching ethical principles; Consider intuitive, emotional, and other nonrational factors; Accept that some problems have elusive solutions, and; Solicit input from colleagues and consultation groups. Numerous vignettes illustrate how to apply positive ethics to many different ethical challenges that psychotherapists will likely encounter in practice"--Publicity materials. (PsycINFO Database Record (c) 2015 APA, all rights reserved).